Safety of indwelling pleural catheter use in patients undergoing chemotherapy: a five-year retrospective evaluation. Issue 1 (December 2016) - Chan Wah Hak, Charleen; Sivakumar, Parthipan; Ahmed, Liju
Abstract Background Indwelling pleural catheters (IPC) are increasingly becoming a first-line treatment in the management of malignant pleural effusions. Ambulatory management using IPC are increasingly used in this patient group whilst they are receiving concurrent chemotherapy. There are currently no prospective trials examining IPC safety in chemotherapy. This study's objective is to determine if IPC insertion is safe in patients undergoing chemotherapy. Methods We conducted a retrospective analysis of all patients who underwent IPC insertion for malignant pleural effusion at our trust from September 2010 to December 2014. Data was collected on IPC insertion and removal, tumour type, systemic chemotherapy, pleural infection and other complications. Results One hundred four patients were identified, 43 in chemotherapy group and 61 in non-chemotherapy group. The incidence of pleural infection in chemotherapy groupvs non-chemotherapy group, 4 (9.3 %)vs 3 (4.9 %) respectively, was not statistically different (Fisher's exactp = 0.311). There was no significant difference in six-month infection-free duration from the date of IPC insertion (log rankp = 0.394). Overall six-month mortality in chemotherapy group was significantly lower than in non-chemotherapy group (log rankp = 0.007). Conclusions This is the second largest retrospective case–control series that concludes systemic chemotherapy is safe in patients with IPC undergoing chemotherapy.